Global Scenarios, Hypotheses and Trends of African Migration Flows in Central America (2010-2022) - Navarro Alvarado, Guillermo Antonio (2024)
The following article analyzes the characteristics and trends of the African migratory flows that transit Central America, problematizing the consensual hypotheses of their origin in Latin America, their mobilities and transits, systematizing and comparing a series of statistical data of their transit through the Darien Region, a description of their mobility patterns and the problematization of the hypotheses in the face of these data. The conclusion of this study refers to a transformation of regional migratory regimes and of the Central American migratory corridor, with the redefinition of its geographical scope, the involvement of global migratory trends and systems, and transformations in migratory policy, framed in growing and diversifying African migratory flows.